Linguistics & biblical exegesis - Mangum, Douglas; Westbury, Josh (Bellingham, WA Lexham Press, 2017)
The Bible was written in ancient Hebrew, Aramaic, and Greek--languages no modern reader can claim to have a native understanding of. But by better understanding how language works, we can understand more from the Bible as we seek to discern the original intent and meaning of each biblical author. In Linguistics & Biblical Exegesis, you will get a basic introduction to the field of linguistics--its history, its key concepts, its major schools of thought, and how its insights can shed light on various problems in biblical Hebrew and Greek. Numerous examples illustrate linguistic concepts, and technical terminology is clearly defined. Learn how the study of language can enhance your Bible study. --
The value of linguistically informed exegesis Michael Aubrey
Includes bibliographical references (pages 203-221) and indexes
Keywords: Bible -- Hermeneutics -- Bible; Hermeneutics; Language and languages -- Religious aspects -- Christianity; Linguistics